Prototype Autocracy (Automatic Transjakarta Security System) - Iqbal, Muhammad; Rozikin, Chaerul; Nuraini, Syifa; Permana, Yusuf A; Subekti, Massus (LPPM Universitas Negeri Jakarta, 2014)
Attempts to sterilize TransJakarta lane has been done, but still less effective. Autocracy is a prototype of latest security system by using the RFID system combined with the Roadblocker. The use of RFID aims to differentiate between Trasnjakarta and other vehicles, while the use of Roadblocker aims to keep inaccessible by other vehicles. With that combination and controlled by a microcontroller system, the lane or busway can only be used for TransJakarta. The stages are done in this research include the study of literature, observation, designing, manufacturing, testing, and refinement. With the Smoothness of busway, TransJakarta can run with optimum speed on the lane and more faster. If TransJakarta could be run faster and cheaper, the people who use personal vehicles will move to TransJakarta and it will reduce the traffic jams in Jakarta.